The Influence of Stakeholder Pressure, Corporate Governance, and Capital Structure on Sustainability Reporting Disclosure with Institutional Ownership as a Moderating Variable - Ni Wayan Murdani; I Putu Gede Diatmika; Desak Nyoman Sri Werastuti (Dinasti Publisher, 2025)
This study aims to analyze the influence of stakeholder pressure, corporate governance, and capital structure on sustainability reporting disclosure, with institutional ownership as a moderating variable. A quantitative research design was employed, with the population consisting of banking sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Samples were selected using a purposive sampling technique, resulting in 32 companies that met the criteria. With five years of observation, a total of 160 financial reports were obtained. Data were collected through documentation studies and analyzed using Moderated Regression Analysis (MRA) with panel data. The results indicate that shareholder pressure, corporate governance, and capital structure have a positive and significant effect on sustainability reporting disclosure among banking companies listed on the IDX during the 2020–2024 period. However, institutional ownership does not moderate the influence of shareholder pressure, corporate governance, or capital structure on sustainability reporting disclosure in these companies.